Jogos digitais e a terceira idade: o herói é o vovô - Mello, Hyldegardes Cavalcanti Castilho de Magalhães (2013)
The growth of digital games in the world open many possibilities of use of digital media. This work intends to analyze how digital games can collaborate on the interaction between the elderly and the communication with the world, the elderly and the elderly with other generations (born in the digital age). From the question "The digital games as a space for interaction and communication can contribute to increased quality in the communication of the elderly to society?". The research developed in this work will be created in dialogue and with multiple authors who write about games and communication, highlighting authors Huizinga (2001), Calois (1990), Branco (2011), Pinheiro (2007) Gularte (2010), Xavier (2010), besides other important authors for this work such as Campbell (2007), Mcluhan (2007), Murray (2003), Morin (2000; 2008; 2011), Teilhard de Chardin (2006) e Barbosa Filho e Castro (2008), The age will be based on the work of Beauvoir (1990) and his thoughts on the aging process. Morin (2005) is also one of the authors on the ageing in modern society, the difficulties of the elderly at a time of new valuation and consequently the devaluation which are deemed obsolete. Other authors who bring significant works in the old theme as Shirmacher (2005), Faleiros and Loureço (2005) and Debert (2004) provide information to learn more about the subject, enabling reflection about points of analysis. The concept of Noosphere of Morin (2008) and Teilhard de Chardin (2006) the author will explain about the creation of the concept of ludosfera as a playful space, birthplace of beings of costumes, the characters of the games that inhabit the imagination of children, youth, adults and seniors. Of texts and reports of references will be deducted points over the rescue of communication and quality of life of older people who use digital games.